PENGARUH PENGGUNAAN E-MONEY TERHADAP MINAT MENABUNG MASYARAKAT USIA PRODUKTIF DI SURABAYA - Ervina Agmarita; Merlyana Dwinda Yanthi (Fakultas Ekonomi Universitas IBA, 2022)
Electronic Money (E-Money) defined as internet-based money or chip-based money which transactions involve internet network users, electronic money is prepaid value which the transaction only done after users make a payment in cash or non-cash. Saving Interest described as an individual's interest in setting aside some money or income and saving on a particular institution or depository. This study was conducted in Surabaya with 160 sample. The type of research conducted is causal associative research with multiple linear analysis statistical test and the approach used in this study is quantitative approach. Independent variables used in this study are the ease in the use of E-Money, the benefits in the use of E-Money, and subjective norms in the use of E-money with the dependent variable saving interest. This study was conducted to determine whether the supporting variables in the use of E-Money has an influence on the interest in saving of Surabaya Citizen. The results showed that the use of E-Money affects the interest in saving people, more specifically the ease variable, and subjective norms are considered to have an influence on the interest in saving people, while the benefit variable is considered to have no influence on the interest in saving people.